Kesetaraan Gender: Langkah Menuju Demokratisasi Nagari - Fatmariza, Fatmariza (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2003)
Otonomi Daerah (Local Autonomy) and back to nagari ought to give room to democratization process specialize in West Sumatra. This matter assumed will guarantee participation all group in local storey; men, and also woman. So far still is slimmest woman concerned in public activity such as institute governance of nagari. Constraint emerge do not only from political side, but also from patriarchy values which still jell. Very strong view about value system, norm, myth, and also stereotype about woman represent ideology resistance. Understanding of this ideology do not only by men but also by woman, they tend to accept still accept concepts which exactly woman marginalization in development. Beside that constraint there is still be other which have the character of material. Among the constraint is, ( 1) Women education still relative lower, (2) Lack of accessing to public policyÂ including in lowest regional storey; ( 3) double burden. Beside as household organizer, impecunious woman also as wage earner, so that they don't have leeway to follow other activity more than anything else activity in public domain Kata Kunci: Kesetaraan Gender, Demokratisasi,Nagari, Patriarkhi, Partisipasi